2020
DOI: 10.1109/tmi.2020.3004648
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CdTe, GaAs, Se and Si as Sensor Materials for Mammography

Abstract: Despite the benefits of mammography investigations, some studies have shown that X-ray exposure from the mammography screening itself can statistically cause breast cancer in a small fraction of women. Therefore, a dose reduction in mammography is desirable. At the same time, there is a demand for a higher spatial resolution in mammographic imaging. The most promising way to achieve these goals is the use of advanced photonprocessing semiconductor X-ray detectors with optimum sensor materials. This study addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In a high-resistivity single crystal form, as studied in this work, it has been used for many years as a detector in gamma-ray astronomy [1][2][3] and recently is attracting interest for medical imaging. 4 A particular advantage of CdTe is direct high-energy photon detection with good stopping power, along with the ability to discriminate the photon-energies in a multi-source spectrum. Recently, CdTe has also been mentioned as a candidate material for direct electron detection, 5 underpinning the need for deeper understanding of electron scattering processes in CdTe.…”
Section: Introductionmentioning
confidence: 99%
“…In a high-resistivity single crystal form, as studied in this work, it has been used for many years as a detector in gamma-ray astronomy [1][2][3] and recently is attracting interest for medical imaging. 4 A particular advantage of CdTe is direct high-energy photon detection with good stopping power, along with the ability to discriminate the photon-energies in a multi-source spectrum. Recently, CdTe has also been mentioned as a candidate material for direct electron detection, 5 underpinning the need for deeper understanding of electron scattering processes in CdTe.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have compared image quality between CdTe and GaAs PCDs in a mammographic setting, the current studies herein are focused to CESM because of the energy range examined. For example, Procz et al 24 evaluated and compared the image quality of CdTe and GaAs PCDs using a mammography phantom and found that the CdTe detector gave better spatial resolution and contrast-to-noise ratios than the GaAs detector. However, the x-ray spectra used in their study was set to 28 kVp.…”
Section: Discussionmentioning
confidence: 99%
“…The newly hybrid photon counting-detectors, developed during the last two decades, such as Medipix [19,20], could impact significantly X-ray direct detection digital mammography. These detectors allow the usage of different semiconductor sensor materials such as Si, GaAs, CdTe, and Cadmium Zinc Telluride (CZT), and are capable of storing information of each single incident X-ray photon, reducing dark current present in charge integration systems, reflecting in images with higher signal-to-noise, higher spatial resolution and allowing single-exposure spectral imaging [21][22][23]. Recently, there have been new X-ray sensor materials under investigation such as perovskite-based semiconductors that deserve also attention for their potential capabilities in digital X-ray mammography [24].…”
Section: Introductionmentioning
confidence: 99%